Evaluasi Kualitas Fisik Lingkungan Tempat Kerja dan Insiden CVS pada Pekerja PT PELINDO III (Persero) - Alfania Mei Larasati; Ulfah Mu'amarotul Hikmah; Ririh Yudhastuti (Universitas Airlangga, 2023)
Background: Computer Vision Syndrome (CVS) is an incident commonly reported and experienced by workers using computers. The Information and Communication Technology staff of PT Pelabuhan Indonesia III are one of those having a high risk of CVS incidents. Objectives: The study aimed to evaluate the workplace's physical environment and the Computer Vision Syndrome (CVS) incidents on staff at the head office of PT Pelabuhan Indonesia III (Persero) under the applicable regulations. Methods: This study employed primary data with the qualitative observational method with a cross-sectional study design. The study utilized two respondent groups, i.e., exposed, comprising 30 ICT staff, and control, comprising 30 HSSE and Port Equipment Engineering staff. The dependent variable of the study was the number of CVS incidents experienced by staff. The independent variable of the study was the workplace physical quality (lighting intensity, temperature, and humidity). Results: The study result demonstrated that the lighting intensity and room temperature of the exposed group did not follow the standard, exposing staff to CVS. In the control group, lighting intensity did not follow the standard, and staff had CVS, the humidity did not follow the standard, and staff did not have CVS, and room temperature followed the standard, and staff did not have CVS. Conclusions: The study concluded non-conformity in the physical environment variable of the workplace under the applicable regulations and is based on predecessor literature studies.